Comparison of multi code link-layer transmission strategies in 3Gwireless CDMA. - Fitzek, F.H.P (IEEE Communications magazine)
Within this article we investigate the possibility of using multiple codes within a code-division multiple access system to reduce the losses in a delay bounded transmission for 3G multimedia applications over wireless links with fading. Multiple codes are used to recover from gaps on the wireless link after a fading period by means of ARQ-type retransmissions. One key feature of our work is that even a small number of multiple codes leads to a dramatic reduction of losses regarding delay bounds of multimedia applications